Pemanfaatan Sistem Informasi Akuntansi dalam Memoderasi Pengaruh Profesionalisme terhadap Kualitas Pelaporan Keuangan di LPD ABIANSEMAL - Rengganis, RR. Maria Yulia Dwi; Bagiana, I Kadek; Dewi, I Gusti Putu Eka Rustiana (Jurnal Akuntansi & Keuangan Unja, 2026)
This study aims to examine the effect of professionalism and accounting information system (AIS) utilization on financial reporting quality, as well as the role of AIS utilization in moderating the relationship between professionalism and financial reporting quality. The research was conducted at Village Credit Institutions (LPDs) in Abiansemal Subdistrict. The sample consisted of 93 respondents. The data were analyzed using simple linear regression and Moderated Regression Analysis (MRA) with SPSS software. The results showed that professionalism has a positive and significant effect on financial reporting quality. However, partially, AIS utilization does not have a significant effect on financial reporting quality in the MRA model. Furthermore, the study proves that AIS utilization significantly moderates (strengthens) the effect of professionalism on financial reporting quality. These findings imply that high professionalism supported by the utilization of accounting systems will produce better financial reports.